2017
DOI: 10.1016/j.bbi.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Lower total and regional grey matter brain volumes in youth with perinatally-acquired HIV infection: Associations with HIV disease severity, substance use, and cognition

Abstract: Despite improved survival due to combination antiretroviral therapy (cART), youth with perinatally-acquired HIV (PHIV) show cognitive deficits and developmental delay at increased rates. HIV affects the brain during critical periods of development, and the brain may be a persistent reservoir for HIV due to suboptimal blood brain barrier penetration of cART. We conducted structural magnetic resonance imaging (sMRI) and cognitive testing in 40 PHIV youth (mean age=16.7 years) recruited from the NIH Pediatric HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 89 publications
(140 reference statements)
0
28
0
Order By: Relevance
“…This is the first study to examine over a narrow age range the impact of HIV on subcortical gray matter and corpus callosum volumes in a cohort of children receiving ART before 18 months of age and VL suppression by 109 weeks in all but three children. In contrast to most previous studies in HIV+ adults and children that reported gray matter atrophy (Tardieu et al, 2000 ; Crain et al, 2010 ; Becker et al, 2011 ; Chang et al, 2011 ; Cohen et al, 2016 ; Musielak and Fine, 2016 ; Lewis-de Los Angeles et al, 2017 ), we found HIV-related subcortical GM volume increases at 5 years in the left GP and bilaterally in the NA and Pu, but CC reductions. Association of increasing age of ART initiation with greater volumes in the Pu suggest that treatment timing plays a role in these observed volume increases.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…This is the first study to examine over a narrow age range the impact of HIV on subcortical gray matter and corpus callosum volumes in a cohort of children receiving ART before 18 months of age and VL suppression by 109 weeks in all but three children. In contrast to most previous studies in HIV+ adults and children that reported gray matter atrophy (Tardieu et al, 2000 ; Crain et al, 2010 ; Becker et al, 2011 ; Chang et al, 2011 ; Cohen et al, 2016 ; Musielak and Fine, 2016 ; Lewis-de Los Angeles et al, 2017 ), we found HIV-related subcortical GM volume increases at 5 years in the left GP and bilaterally in the NA and Pu, but CC reductions. Association of increasing age of ART initiation with greater volumes in the Pu suggest that treatment timing plays a role in these observed volume increases.…”
Section: Discussionmentioning
confidence: 60%
“…Even though most studies in children find cortical and total gray matter atrophy in HIV infection (Cohen et al, 2016 ; Lewis-de Los Angeles et al, 2017 ), regional GM volume increases have been reported (Sarma et al, 2014 ). Although, few studies have examined subcortical volumes specifically, two recent studies reported HIV-related regional subcortical GM increases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we look forward to make a comparison of the algorithms for detecting other human brain-related diseases, such as sickle cell disease [25], HIV disease [26], etc. Some image preprocessing methods [27][28][29][30][31][32][33][34] may be added to check the performance.…”
Section: Discussionmentioning
confidence: 99%